Linking increased returns to industry-level change : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Business and Administration in Strategy at Massey University, Palmerston North, New Zealand - Obren, Mark (Massey University, 2006)
While the change literature is currently dominated by the punctuated equilibrium paradigm, anomalies have appeared to the paradigm in the form of high velocity change and hypercompetition. D'Aveni (1999) reconciles these anomalies with the punctuated equilibrium paradigm by suggesting that the frequency of change experienced affects the change experienced. This research considered whether the presence of increasing returns in an industry is correlated with the frequency of change experienced by the industry and the types of change that appear, thus providing an explanation for the differing forms of change. A second observation in the literature is that an industry experiences a period of instability after a discontinuity. This research considered whether the temporal proximity or type of a preceding discontinuity influenced the likelihood or type of later discontinuities. A longitudinal study identified discontinuities in nine industries throughout the industries' histories. The industries were categorised as: increasing returns, derived from external network effects (Airlines, Data Communications, Electricity and Shipping Lines), complementarity (Information Storage) or information content (Software), respectively; or as constant returns (Aircraft Manufacturing, Telecommunications Manufacturing and Shipbuilding). A comparison of discontinuities has been made between pairs of industries with a common end-user of the industry outputs, where one industry exhibits increasing returns and the companion industry has constant returns, using Binomial Distribution, Fisher's Exact Test and Generalised Linear Modelling techniques. Further Generalised Linear Models tested the interactions of discontinuities. Industries with increasing returns were found to have greater frequency of change. The types of change experienced were found to affect subsequent change, with both types of discontinuities being correlated with increased proportions of competency-enhancing change for ten years, while competency-destroying and competency-enhancing discontinuities were associated with increased frequency of change for twenty and ten years, respectively. The evidence associating increasing returns with competency type was unreliable. Consequently, increasing returns industries may experience a greater variation of frequency of change, with industries entering and leaving periods of enhanced frequencies of change. Thus, industries with increasing returns are more likely to experience change consistent with hypercompetition and high velocity conditions, compared with the punctuated equilibrium style change experienced by constant returns industries.
Keywords: Discontinuities; Organisational change; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management